Establishing levels of competence in translation: First results of the nact project - Albir, Amparo Hurtado; Galán-Mañas, Anabel; Olalla-Soler, Christian; Rodríguez-Inés, Patricia; Romero, Lupe; Kuznik, Anna; de Talita Serpa, Tradução [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2020)
This paper presents the research project the PACTE group is carrying out on Establishing Competence Levels in the Acquisition of Translation Competence in Written Translation. The project aims to propose level descriptors as a first step towards developing a common European framework of reference for translation's academic and professional arenas. The project is a continuation of PACTE's previous experimental research on translation competence and its acquisition. Representatives of both academic and professional arenas participate in the project. It is organized into three stages, the first of which involved the production of a first level descriptor proposal, including a three-level scale with sub-levels and five descriptive categories (language competence; cultural, world knowledge, and thematic competence; instrumental competence; translation service provision competence; and translation problem solving competence). This proposal produced is to be evaluated by experts from the academic and professional arenas. This paper sets out the project, as well as the first level descriptor proposal.
O estabelecimento de níveis de competência em tradução: Primeiros resultados do projeto nact
Keywords: Competence levels; Descriptor scales; European framework; Translation competence; Translation competence acquisition